Review of the Accuracy of the ICD-10 Diabetes Mellitus Diagnosis Code in Outpatient Medical Records at the Taram Health Center, Lima Puluh Kota Regency: Tinjauan Ketepatan Kode Diagnosis Icd-10 Diabetes Melitus Pada Rekam Medis Rawat Jalan Di Puskesmas Taram Kabupaten Lima Puluh Kota - Oza Ornela; Maisa Putra, Deni; Dian Novita; Ade Wisandra; Devid Leonard (Jurnal Rekam Medis dan Informasi Kesehatan, 2025)
Code accuracy refers to the alignment among the code for diagnosis assigned by the coding personnel and the diagnosis documented in the patient's medical records, complying with the guidelines set forth in ICD-10 regulations. Derived from the initial survey conducted by researchers, 8 (80%) of the diagnosis codes were found to be incorrect, while 2 (20%) of the codes were correct. The primary objective of this research was to assess the precision of the ICD-10 code for diabetes mellitus recorded in the outpatient medical documents at the Taram Community Health Center, Limapuluh Kota Regency. This study adopts a descriptive approach employing quantitative methodologies. The initial population encompassed 92 medical record files, whereas the study focused on analyzing 48 of these files as a sample with the technique used was Accidental Sampling. This study was conducted through observational methods employing a structured checklist table for data collection, and the information underwent analysis univariately using a computer. The results of the univariate analysis of 48 medical record files showed that the accuracy of coding incorrect disease diagnoses was 35 (72.9%), the clarity of writing illegible disease diagnoses 15 (31.3%) and the completeness of writing incomplete disease diagnoses 15 (31 .3%). From the findings obtained, the assessment of the diagnosis code's precision remained inadequate, because incorrect diagnosis codes were still found. Therefore, it is recommended that community health centers in implementing coding pay more attention to coding methods so that codes are more precise and accurate in accordance with ICD-10. Kata kunci: Diabetes Mellitus; ICD-10; Accuracy; Code